Post-vibration activity of electrochemically activated water - O. V. Slatinskaia; G. O. Stepanov; O. V. Fartushnaya; E. V. Zubkov; A. D. Zatykina; O. M. Gizitdinova; N. S. Karpov; A. V. Smirnov; V. S. Boriskin; N. N. Rodionova; A. O. Petrova (Тонкие химические технологии, 2025)
Objectives. It was recently discovered that water samples with modified physicochemical properties can be obtained by successive vibration treatment of intact water together with a solution of a substance located in separate closely spaced vials. We refer to such samples as iterations. By adding the vibrational iterations into the initial substance, the physicochemical properties of the latter are changed, i.e., they demonstrate post-vibration activity. In addition, it has been shown that vibrational iterations can be obtained using water treated with a magnetic field as the initial substance. On this basis, we may hypothesize that the phenomenon of post-vibration activity is universal. To confirm this hypothesis, water treated with an electric signal having various parameters (electrochemically activated water) was used as the initial substance for the preparation of vibrational iterations.Methods. The physicochemical properties of vibrational iterations, which were obtained from electrochemically activated water, were studied by conductometry, terahertz spectroscopy, and radiometry. The effect of the initial substance or its vibrational iterations on intact water (a neutral carrier) was evaluated by dynamic light scattering. For this purpose, the intensity of light scattering by the sample and the hydrodynamic diameter of optical heterogeneities were measured. The attenuation coefficient of an additional electric signal applied to the samples was determined.Results. The obtained vibrational iterations differ from intact water and their mixtures with intact water in terms of specific electrical conductivity, power flux density of microwave radiation, as well as in the contribution of the main (Debye) relaxation process to the overall dielectric response. Mixtures of vibrational iterations with water also differ from intact water in terms of the size of optical heterogeneities. By analogy with the vibrational iterations for which solutions of high- and low-molecular-weight substances were used as the initial substance, vibrational iterations obtained using electrochemically activated water can be classified into different groups (fractions) according to their physicochemical characteristics. Different degrees of changes in the physicochemical characteristics are observed depending on the parameters of the electric signal used to obtain the initial substance. The efficiency of electrical signal propagation in these mixtures, as estimated by the signal strength attenuation coefficient, is additionally changed. The addition of the initial substance (electrochemically activated water) to intact water also leads to changes in the physicochemical properties of the resulting mixture compared to the control. Depending on the parameters of the electric signal used to obtain the initial substance, the magnitude of changes in the physicochemical characteristics of these mixtures similarly varies.Conclusions. The fundamental possibility of obtaining vibrational iterations from electrochemically activated water similarly to vibrational iterations prepared in other studies, was demonstrated. This confirms the universality of the phenomenon of post-vibration.